Shopping Products Online After the COVID-19 Era - Yasintha Soelasih; Sumani Sumani (Binus Business Review, 2024)
The COVID-19 pandemic has changed consumer purchase behavior. The research observed consumer behavior in purchasing online products after the pandemic. It focused on attitudes, perceived behavior control, and financial and product risks. They influenced purchase decisions, resulting in customer satisfaction and repurchase intention in online shopping. The research applied a quantitative method. Data collection used online research. It managed to get 443 respondents. The study was conducted in Indonesia with respondents who had done online shopping. The hypothesis test was done using Structural Equation Modeling (SEM) with Smart-PLS software. The research results show that H1, H1a, H1b, H2, H2a, H2b, H3, H3a, H3b, H5, H6, H6a, H6b, and H7 are accepted. Meanwhile, H4, H4a, and H4b are rejected. The hypothesis test results show an influence between attitudes, perceived behavior control, and financial risk on customer satisfaction and repurchase intention through purchase decisions both directly and indirectly. Meanwhile, product risk does not directly or indirectly influence customer satisfaction and repurchase intention through purchase decisions. In conclusion, financial risk is the most influential factor in purchase decisions. If the financial risk is low, customers’ purchase decisions will be high. The research contributes to consumer behavior, especially regarding online shopping. Consumers purchasing online products pay attention to the processes of clarity, assurance, security, comfort, and trust.